Clonal and seasonal genetic variation of major oil components of Salvia fruticosa Mill. - Fatma Uysal; Muharrem Golukcu; Murat Alan; Esra Alim; Kenan Turgut (Horticultural Science)
Anatolian sage (Salvia fruticosa Mill.) is widely used in many food, cosmetics, and pharmaceutical sectors. This study aimed to determine the differences in essential oil components and seasonal changes in the components of six clonally selected C-clones and one natural population in a randomized block design with three replications. Samples were collected monthly from C-clones for two years, and essential oil rates were determined. Clonal heritability was between 0.00 and 0.78. When the best clone was selected from six clones, the genetic gain changed from 12.4 to 44.8 for the essential oil components. Assessment of all clones revealed that the time of monthly harvests significantly affected essential oil components. The clone and harvest time interaction caused significant differences in essential oil components, and clones reached the highest values in different months. The correlation analysis showed a significant negative association between camphor and "β-pinene and β-caryophyllene" and a positive association between camphor and essential oil. High variation in the components, the differences in harvest times, and high correlations between components indicated that clones developed by selection have a significant production potential.